The Chartists : perpectives & legacies - Chase, Malcolm (Monmouth, 2015)
"This book explores some of the main channels and by-ways in the history of Chartism - both in the UK and the wider world - it considers: - The place of Chartism within the wider framework of Victorian politics - The Chartist Land Plan - The impact of Canada’s 1837-8 rebellions on Chartism - Chartism’s endurance in Wales beyond the 1839 Rising - The role of children in Chartist campaigning - Key questions in Chartist historiography - Chartism’s impact on the mid-Victorian ethos of ‘self-help’, and on the workings of parliamentary democracy